2023
DOI: 10.3390/jcm12030752
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-Inhibitor-Induced Hypomagnesemia in Kidney Transplant Patients: A Monocentric Comparative Study between Sucrosomial Magnesium and Magnesium Pidolate Supplementation

Abstract: Magnesium (Mg) contributes to DNA stability, protein synthesis and cardiac excitability, while Mg deficiency leads to increased cardiovascular mortality, diabetes, hyperparathyroidism and risk of fractures. In kidney transplant patients, calcineurin inhibitors (CNIs) downregulating Mg channel TRPM6 in the distal collecting tubule induce early hypomagnesemia (HypoMg), which is associated with a faster decline in allograft function. A new formulation, sucrosomial Mg (SucrMg), for oral supplements encapsulates Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Indeed, after analysis of various factors, only the use of CNI correlated statistically significantly with hypomagnesemia. CNI induces hypomagnesemia through urinary Mg 2+ wasting by downregulating the renal expression of the epidermal growth factor (EGF) and the Mg 2+ channel Transient Receptor Potential Pelastatin 6 (TRMP6) in the distal collecting tubule ( 1 , 22 ). The incidence of tacrolimus- or cyclosporine-induced hypomagnesemia has been studied in-depth, and these common side effects are now well known in the medical world ( 20 , 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, after analysis of various factors, only the use of CNI correlated statistically significantly with hypomagnesemia. CNI induces hypomagnesemia through urinary Mg 2+ wasting by downregulating the renal expression of the epidermal growth factor (EGF) and the Mg 2+ channel Transient Receptor Potential Pelastatin 6 (TRMP6) in the distal collecting tubule ( 1 , 22 ). The incidence of tacrolimus- or cyclosporine-induced hypomagnesemia has been studied in-depth, and these common side effects are now well known in the medical world ( 20 , 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that hypomagnesemia is associated with unfavorable outcomes and mortality ( 21 , 22 ). Favoring iMg 2+ over tMg 2+ could enhance the detection of hypomagnesemia, enabling more accurate identification of patients in need of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia is a common finding in most patients after kTx, particularly during the initial period. The use of calcineurin inhibitors, notably tacrolimus, tends to contribute to its occurrence [58]. What is more, patients who have undergone kTx may experience fluctuations in serum potassium levels, including both low and high values.…”
Section: Introductionmentioning
confidence: 99%